Comparative study of magnetite nanoparticles obtained by pulsed laser ablation in water and air - Svetlichnyi, Valerii A.; Shabalina, Anastasiia V.; Lapin, Ivan N.; Goncharova, Darya A.; Kharlamova, Tamara S.; Stadnichenko, Andrey I. (Applied surface science)
Magnetic nanomaterials were synthesized using a method of pulsed laser ablation of an iron target in water (PLAL) and in air (PLAG). The microstructure and composition of the obtained materials differed. Spherical nanoparticles (NPs) of 2-80 nm containing Fe 3 O 4 , α-Fe 2 O 3 , γ-Fe 2 O 3 , FeO and Fe were obtained using PLAL. According to the XPS and FTIR data, the surfaces of these particles contained both Fe 3 O 4 and Fe 2 O 3 . PLAG led to the formation of NPs of 2-120 nm and 2-D lamellar structures up to 1 μm. This material contained more magnetite and nitrogen species, presumably iron nitrides. This material's surface contained FeOOH; the OH-group content was very high. It exhibited the greatest sedimentation stability and zeta potential value, while magnetic NPs (MNPs) obtained in water were less stable in colloids. The difference in the magnetic parameters of the two materials can be connected to not only the different composition (different magnetite content and nitrogen species presence) but also their structural features. Thus, PLAL and PLAG methods allowed for obtaining magnetic nanostructured materials with different characteristics suitable for application in different fields. © 2018 Elsevier B.V.